Brain white matter microstructure in obese women with binge eating disorder. (23rd July 2020) - Estella, Nara Mendes; Sanches, Liana Guerra; Maranhão, Mara Fernandes; Hoexter, Marcelo Queiroz; Schmidt, Ulrike; Campbell, Iain C.; Amaro, Edson; Claudino, Angélica Medeiros
Abstract: Objective: Research on potential brain circuit abnormalities in binge eating disorder (BED) is limited. Here, we assess white matter (WM) microstructure in obese women with BED. Method: Diffusion tensor imaging data were acquired, and tract‐based spatial statistics used to examine WM in women with BED who were obese ( n = 17) compared to normal‐weight (NWC) ( n = 17) and to women who were obese (OBC) ( n = 13). Body mass index (BMI) was a covariate in the analyses. Results: The BED group (vs. NWC) had greater axial diffusion (AD) in the forceps minor, anterior thalamic radiation, superior and inferior longitudinal fasciculus, that is, in pathways connecting fronto‐limbic regions. Microstructures differences in AD between the BED and OBC groups were seen in fronto‐limbic pathways extending to temporoparietal pathways. The BED (vs. OBC) group had greater fractional anisotropy in the forceps minor and greater AD in the superior longitudinal fasciculus, cingulate gyrus, and corpus callosum, consistent with fronto‐tempoparietal pathways. Conclusion: Women with BED show WM alterations in AD in fronto‐limbic and parietal pathways that are important in decision‐making processes. As BMI was a covariate in the analyses, alterations in BED may be part of the pathology, but whether they are a cause or effect of illness is unclear. Highlights: Women with binge eating disorder (BED) who are obese (compared to normal‐weight women and also to women who are obese) showed white matter (WM) alterations in neural pathways that are important in decision‐making processes. Differences in WM between the BED and normal‐weight group were seen in pathways with fronto‐limbic connections and differences in WM between the BED and obese group extended to pathways with temporoparietal connections. As we corrected for body mass index, the WM changes that are specific to the BED group may be part of BED pathology: whether they are a cause or effect of illness is unclear.